Development of Marketing Channels for Tai Khun Products at Wat Chiang Yuen Learning Center, University of the Third Age Chiang Rai City, Chiang Rai Province - Wongpan, Surapong; Fung-Fuang , Thanyaporn (Area Based Development Research Journal, 2022)
The University of the Third Age in Chiang Rai city, Muang district, Chiang Rai province supports the elderly people to produce Tai Khun handmade products which are part of their learning process. However, they experience problems regarding low selling volume because of the lack of appropriate packaging and communication channels with their target customers. This research aims to develop packaging, marketing channels, and marketing communication for Tai Khun products. The method deployed a focus group discussion with 30 participants. A questionnaire is distributed for the field survey to 400 participants and the data were analyzed. The procedure involved 1) analyzing the potential of the learning center, 2) designing packaging, 3) analyzing consumer behaviors, 4) developing marketing channels, and 5) developing marketing communication. The results include the designed packaging prototypes for five products, which are flower containers, zodiac flags, small Lanna flag, golden and silver flower container, and stencil cloth. Two platforms of marketing channels have also been developed. The online version uses Facebook Page. The off-line onsite shop at the temple utilizes a prefabricated and relocatable structure. For marketing, two marketing communications were established. The offline application utilizes a person as an announcer presenting the products by storytelling about packaging and label using red, gold, and black colors, which reflect the red temple and characteristics of Tai Khun. Finally, the online platform relies on the Facebook Page which creates a perception among the target customers and thus generates an increased sales volume of at least 15%.